Urgensi Filsafat Pendidikan dalam Membentuk Karakter Siswa SMA di Kota Bontang - Munir, Munir (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
Philosophy is a path to living life with compassion and love. Compassion and love inevitably foster wisdom and virtue. This study explores the role of educational philosophy in shaping the character of high school students in Bontang City. Amidst the currents of globalization and the moral challenges faced by the younger generation, educational philosophy serves as a foundation for critical, ethical, and reflective thinking in the educational process. This research employs a qualitative-descriptive approach through literature review and contextual analysis in Bontang. The findings indicate that educational philosophy plays a strategic role in instilling local wisdom values, fostering self-awareness, and enhancing students’ moral character. Therefore, integrating educational philosophy into the curriculum and learning practices at the high school level is essential to produce graduates who are not only intellectually capable but also morally and spiritually mature.